2005
DOI: 10.1007/s10811-005-6625-x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid and fatty acid yield of nine stationary-phase microalgae: Applications and unusual C24–C28 polyunsaturated fatty acids

Abstract: Nine microalgal species from the classes Bacillariophyceae, Cryptophyceae, Prymnesiophyceae and Dinophyceae were isolated from Australian waters, cultured to stationary phase and analyzed for their lipid and fatty acid composition and yield. Five species (Pavlova pinguis, Heterocapsa niei, Proteomonas sulcata, Navicula jeffreyi and Thalassiosira pseudonana) produced high proportions of triacylglycerol (TAG: 22-57% total lipid). An unidentified Navicula-like diatom (CS-786), despite having a low TAG content, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(68 citation statements)
references
References 55 publications
5
60
1
2
Order By: Relevance
“…Although many studies have demonstrated accumulation of (neutral) lipids in starved cultures of microalgae, relatively little was known about the effect of growth phase on EPA and DHA accumulation. Our study confirms previous results that the absolute amounts of EPA and DHA, but also the total fatty acid content varies considerably between species (Volkman et al 1989;Viso and Marty 1993;Tonon et al 2002;Mansour et al 2005;Patil et al 2007;Boelen et al 2013). Consequently, high interspecific variability in their nutritional value exists.…”
Section: Discussionsupporting
confidence: 91%
“…Although many studies have demonstrated accumulation of (neutral) lipids in starved cultures of microalgae, relatively little was known about the effect of growth phase on EPA and DHA accumulation. Our study confirms previous results that the absolute amounts of EPA and DHA, but also the total fatty acid content varies considerably between species (Volkman et al 1989;Viso and Marty 1993;Tonon et al 2002;Mansour et al 2005;Patil et al 2007;Boelen et al 2013). Consequently, high interspecific variability in their nutritional value exists.…”
Section: Discussionsupporting
confidence: 91%
“…Reports range from 4 to 32% C14:0 of the total FA composition for diatoms [98,103,104]. C16 FAs are highly represented in diatoms and C16:0 and C16:1 combined can represent 65-70% of the total FA, with C16:1 being predominant.…”
Section: Key Termmentioning
confidence: 99%
“…Diatoms are unusually highly enriched for eicosapentaenoic acid (EPA; C20:5, w-3), which is not prevalent in chlorophytes [98,103,104]. Fish do not naturally produce EPA, but obtain it from algae they ingest, to which diatoms should contribute significantly.…”
Section: Other Valuable Hydrocarbons Epa Dha and Isoprenoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Algunos ensayos realizados previamente, demostraron que la tasa de renovación utilizada en esta investigación era satisfactoria, coincidiendo con lo expuesto por Otero et al (1997), lo cual permitió obtener durante la fase de estabilización en ambos medios de cultivo a 180μE/m 2 .s, densidades celulares superiores y tasas específicas de crecimiento similares a las reportadas por Mansour et al (2005). A pesar de que el crecimiento de T. pseudonana en Humus a 60 y 120μE/m 2 .s fue bajo, el efecto combinado de éste, con el incremento de la irradiancia permitió la mayor producción de biomasa.…”
Section: Resultsunclassified